Production of reference sources of radioactive aerosols in filters for proficiency testing. (January 2015) - Monsanglant-Louvet, C.; Osmond, M.; Ferreux, L.; Liatimi, N.; Maulard, A.; Picolo, J.L.; Marcillaud, B.; Gensdarmes, F.
Abstract: In the framework of the organization of proficiency testing, filters with deposits of 137 Cs and 90 Sr+ 90 Y radioactive aerosols have been submitted to laboratories for radionuclide measurement. Procedures for the special preparation and characterization of filters have been developed. The different steps of filter preparation, determination of the deposited radionuclide activity and characterization of the homogeneity of these deposits are presented. This method of filter preparation can also be used in the production of secondary standards, whose properties are more adapted to the needs of laboratories measuring radioactivity in filters than are the solid sources that they typically use. Highlights: Proficiency testing campaigns organized by IRSN. Special preparation and characterization of filter sources. Production bench description for aerosols calibrated for size and activity. Measuring filters and assigned values.